Improvement of Yield and Its Related Traits for Backbone Hybrid Rice Parent Minghui 86 Using Advanced Backcross Breeding Strategies - Hong-jun ZHANG; Hui WANG; Guo-you YE; Yi-liang QIAN; Ying-yao SHI; Jia-fa XIA; Ze-fu LI; Ling-hua ZHU; Yong-ming GAO; Zhi-kang LI (Journal of Integrative Agriculture, 2013)
How to overcome yield stagnation is a big challenge to rice breeders. An effective method for quickly developing new cultivars is to further improve an outstanding cultivar. In this study, three advanced backcross populations under yield selection that consist of 123 BC2F2:4 introgression lines (ILs) were developed by crossing Minghui 86 (recurrent parent, RP) with three high-yielding varieties (donors), namely, ZDZ057, Fuhui 838, and Teqing, respectively. The progeny testing allowed the identification of 12 promising ILs that had significantly higher mean grain yields than Minghui 86 in two environments. A total of 55 QTLs that affect grain yield and its related traits were identified, which included 50 QTLs that were detected using the likelihood ratio test based on stepwise regression (RSTEP-LRT) method, and eight grain yield per plant (GY) QTLs were detected using chi-squared (c2) test. Among these QTLs, five QTLs were simultaneously detected in different populations and 22 QTLs were detected in both environments. The beneficial donor alleles for increased GY and its related traits were identified in 63.6% (35 out of 55) of the QTLs. These promising ILs and QTLs identified will provide the elite breeding materials and genetic information for further improvement of the grain yield for Minghui 86 through pyramiding breeding.